Antiherpetic efficacy of aqueous extracts of the cyanobacterium Arthrospira fusiformis from Chad - Sharaf, Mona M.; Amara, A.; Aboul-Enein, A.; Helmi, S.; Ballot, A.; Schnitzler, Paul (Die Pharmazie, 2013)
Natural substances offer interesting pharmacological perspectives for antiviral drug development with regard to broad spectrum antiviral properties and novel modes of action. Drugs currently used to treat cutaneous or genital herpetic infections are effective in limiting disease, but - the emergence of drug-resistant viruses in immunocompromised individuals can be problematic. A nontoxic cyanobacterium Arthrospira strain from Chad has been characterized by sequence analysis of the intergenic spacer region of the phycocyanin gene. This cyanobacterium was identified - as Arthrospira fusiformis by phylogenetic tree analysis. The antiherpetic activity of crude aqueous extracts from the Chad A. fusiformis isolate was determined. Antiviral efficacy against herpes simplex virus of cold water extract, hot water extract and phosphate buffer extract - was assessed in plaque reduction assays and their mode of antiherpetic action was analysed. In virus suspension assays, cold water extract, hot water extract and phosphate buffer extract inhibited virus infectivity by 54.9%, 64.6%, and 99.8%, respectively, in a dose-dependent manner. The mode - of antiviral action was determined by addition of cyanobacterial extracts separately at different time periods during the viral infection cycle. Extracts of A. fusiformis strain clearly inhibited herpesvirus multiplication before and during virus infection of host cells. The phosphate - buffer extract of the A. fusiformis strain affected free herpes simplex virus prior to infection of host cells and inhibited intracellular viral replication. It is concluded, that Arthrospira compounds warrant further investigation to examine their potential role in the treatment - of herpetic infections.
Gesehen am 13.09.2021